Human–robot collaborative partial destruction disassembly sequence planning method for end-of-life product driven by multi-failures. (January 2023) - Guo, Lei; Zhang, Zeqiang; Zhang, Xiufen
Abstract: Partial destructive disassembly (PDD) of large complex products often requires human–robot collaborative disassembly (HRCD). Therefore, a human–robot collaboration partial destructive disassembly sequence planning (HRCPDDSP) method of end-of-life products driven by multiple failures is proposed to obtain the optimal disassembly sequence to improve disassembly efficiency and degree of automation. Based on the product disassembly priority and part failure characteristics, an information model of the HRCPDDSP method is constructed. Furthermore, the model is expressed as a constraint matrix and recycling decision matrix. A multi-layer chromosome coding method, including HRCD, destructive constraint, and node layers, is proposed of the characteristics of the HRCPDDSP method. The approximate optimal sequence of human–robot collaboration PDD is achieved by improving evolutionary mechanisms such as selection, crossing, and mutation. Finally, the model and algorithm are applied to solve a case of HRCPDDSP, and the feasibility and effectiveness of the proposed method are further verified by comparison with other disassembly modes.